2011
DOI: 10.1063/1.3567915
|View full text |Cite
|
Sign up to set email alerts
|

Electrode dependence of filament formation in HfO2 resistive-switching memory

Abstract: This study investigates bipolar and nonpolar resistive-switching of HfO 2 with various metal electrodes. Supported by convincing physical and electrical evidence, it is our contention that the composition of conducting filaments in HfO 2 strongly depends upon the metal electrodes. Nonpolar resistive-switching with the Ni electrode is attributed to the migration of metal cations and the corresponding electrochemical metallization. Conversely, oxygen-deficient filaments induced by anion migration are responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(163 citation statements)
references
References 24 publications
6
154
0
Order By: Relevance
“…Based on the phenomena described above, the resistive switching behaviors are agreement with conductive filament model very well. Generally speaking, there are metal CF 27,35-37 and oxygen vacancy CF [38][39][40] in the binary oxide dielectric such as HfO 2 film. Many studies have been reported that active electrodes such as Ag 4,41 and Cu [35][36][37] tends to migrate and form CF connecting with counter electrodes, playing an important role in resistive switching process.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the phenomena described above, the resistive switching behaviors are agreement with conductive filament model very well. Generally speaking, there are metal CF 27,35-37 and oxygen vacancy CF [38][39][40] in the binary oxide dielectric such as HfO 2 film. Many studies have been reported that active electrodes such as Ag 4,41 and Cu [35][36][37] tends to migrate and form CF connecting with counter electrodes, playing an important role in resistive switching process.…”
Section: Resultsmentioning
confidence: 99%
“…1c suggests that some grain boundaries may carry some hopping current at voltages smaller than the SET voltage; this is possible if the environment of O sites happens to be more uniform than average and barriers for conduction may be smaller; see below for more detailed analysis of hopping conduction). We note that the conductive channels are not true metallic filaments as often suggested [11,12]. The hopping current is turned on by a high voltage and the grain boundaries behave as true nanovaristors.…”
mentioning
confidence: 99%
“…In electronics industry, hafnium oxide-based material is currently used as an excellent high-k gate dielectric [1] and oxygen-deficient hafnium oxide also received additional interest for resistive-switching memories [2]. As for other applications, even though the hardness of hafnia (HfO 2 ) is not that high for it to be considered as a superhard material [3], it still attracts attention as a potential candidate for hard oxide-based materials [4].…”
Section: Introductionmentioning
confidence: 99%